2020
DOI: 10.1097/brs.0000000000003442
|View full text |Cite
|
Sign up to set email alerts
|

Cost–Utility Analysis of rhBMP-2 Use in Adult Spinal Deformity Surgery

Abstract: Study Design. Economic modeling of data from a multicenter, prospective registry. Objective. The aim of this study was to analyze the cost utility of recombinant human bone morphogenetic protein-2 (BMP) in adult spinal deformity (ASD) surgery. Summary of Background Data. ASD surgery is expensive and presents risk of major complications. BMP is frequently used off-label to reduce the risk of pseudarthrosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…However, these rates were signi cantly lower in the V-CBA group among patients receiving single-level treatments only (Table 3), in spite of the fact that the VCBA group had statistically higher rates of initial comorbidities with the potential to negatively impact clinical outcomes. The low rate of subsequent lumbar fusion with rhBMP-2 is a frequentlycited bene t over ICBG and a principal justi cation of its cost [11,13,27]. As such, the performance of VCBA in this study is notable, especially in light of the substantially lower average initial hospitalization charges observed for V-CBA patients, and in spite of the higher level of initial comorbidities in this group.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, these rates were signi cantly lower in the V-CBA group among patients receiving single-level treatments only (Table 3), in spite of the fact that the VCBA group had statistically higher rates of initial comorbidities with the potential to negatively impact clinical outcomes. The low rate of subsequent lumbar fusion with rhBMP-2 is a frequentlycited bene t over ICBG and a principal justi cation of its cost [11,13,27]. As such, the performance of VCBA in this study is notable, especially in light of the substantially lower average initial hospitalization charges observed for V-CBA patients, and in spite of the higher level of initial comorbidities in this group.…”
Section: Discussionmentioning
confidence: 78%
“…In spite of serious complications attributed to rhBMP2 in the spine (eg, wound complications, retrograde ejaculation in males, and heterotopic ossi cation) [9,10], several clinical studies have demonstrated that rhBMP-2 in lumbar fusion surgeries increases fusion rates compared to ICBG, while also decreasing fusion time and refusion rates [11]. However, rhBMP-2 remains relatively expensive [12,13] and some thirdparty payers have become increasingly unwilling to reimburse for its prevalent off-label use, leading to downward trends in its overall use from all-time highs in 2009 [7,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of rhBMP-2 is almost universally reported to increase hospitalization costs [6,12,13,[25][26][27], the cause of these large disparities is unknown, as they cannot be explained by direct product costs alone. A de nitive answer to this question is beyond the scope of this study; however, an exploration of potential causes is warranted, albeit speculative.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of serious complications attributed to rhBMP-2 in the spine (eg, wound complications, increased myelopathy/radiculopathy, and heterotopic ossi cation) [9,10], several clinical studies have demonstrated that rhBMP-2 in lumbar fusion surgeries increases fusion rates compared to ICBG, while also decreasing fusion time and refusion rates [11]. However, rhBMP-2 remains relatively expensive [12,13] and some third-party payers have become increasingly unwilling to reimburse for its prevalent off-label use, leading to downward trends in its overall use from all-time highs in 2009 [7,14].…”
Section: Introductionmentioning
confidence: 99%